Length and Width Correlations in Centrobolus Cook, 1897 - Cooper, Mark (New Visions in Biological Science Vol. 9, 2022)
The forest genus of diplopods belonging to the order Spirobolida found along the eastern coast of southern Africa was tested for size correlations. Four morphometric factors for male and female lengths (mm) and widths (mm) were extracted from literature and checked for correlations with each other using the Pearson Correlation Coefficient Calculator. Positive correlations were found in an analysis of 22 species of Centrobolus. Strong positive correlations between male and female lengths and widths were found. There was a moderate positive relationship between female length and male width (r=0.72, Z score=3.91, n=22, p<0.01). There was a positive relationship between male length and female width (r=0.62, Z score=3.16, n=22, p<0.01). Male length/female length correlation differed from male length/female width correlation (z=1.93, n=22, 22, p=0.05).